STRATEGI KOMUNIKASI MEMBANGUN KEMANDIRIAN PANGAN - Parlaungan Adil Rangkuti (Badan Penelitian dan Pengembangan Pertanian, 2009)
Communication strategy in developing food independencyRole of agricultural development communication is important to build food self-suffiency and diversification as the main base of food independency and food security. Food independency will be accomplished if its development comes from people initiative as an awareness to build modern farm industry with effective and efficient communication strategy support. Adoption of innovation technology by means of communication will boost productivity and product quality, decrease loss of production, increase value added of production with farmer empowerment and participation approach, and strengthen farmers' institutions and competitiveness. To empower the farmers, development of single commodity agribusiness cooperation such as rice or maize will facilitate transformation of information on technology and farm management from variety of sources for the farmers. Government policy to develop centers of agricultural information at production centers as agribusiness development area is required to build food independency and food diversification based on local production with effective communication system support. Communication information system based on cooperation and social capital with stakeholders partnership approaches (government, businessmen, university, research and development institutions, social institutions, etc) will accelerate accomplishment of food independency in suburb areas.